Developing a Dental Scrubs Ceremony to define professional identity and teach professionalism to dental undergraduates; lessons learned. (13th April 2018) - Neville, P.; McNally, L.; Waylen, A.
Abstract: Introduction: The UK General Dental Council stipulates that professionalism is a key aspect of the teaching and training of dental students. However, dental educators highlight that teaching dental student's professionalism can be challenging and students often rate this teaching activity negatively. This article documents a teaching initiative at one UK Dental School that aimed to strengthen the professionalism curriculum by introducing a Dental Scrubs Ceremony for second‐year students. Materials and method: The Dental Scrubs Ceremony is inspired by the White Coat Ceremonies that medical students have in universities in North America. It marks the students' first step in their professional and clinical development, with the signing of a pledge of conduct and public presentation of dental scrubs to each student. We report student feedback questionnaire data over a three‐year period together with reflections on the merits and limitations of this alternative approach to teaching professionalism. Results: Student evaluation data show that the perceived usefulness and worthwhileness of a Dental Scrubs Ceremony have grown since its inception in 2015. Most students enjoyed the symbolism of the ceremony, receiving their dental scrubs in a formal event. However, there was mixed evaluation for its effectiveness to teach professionalism. Conclusion: A Dental Scrubs Ceremony is a useful addition to the formal curriculum of professionalism in a dental school. It provides dental students with an opportunity to be inducted into the dental profession as novice dental students starting out on their professional career.